2015
DOI: 10.1007/s00167-015-3645-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal rate of intraoperative and postoperative implant positioning outliers using “MRI-based patient-specific” compared to “computer assisted” instrumentation in total knee replacement

Abstract: Randomized control trial, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Pfitzner et al reported similar findings, with tibial component alignment of 1.0°, with a 3% outlier (±3°from neutral) rate, and femoral component alignment of 1.0°, with a 3% outlier (±3°from [32,42]. Some of the variability in results may relate to particular surgical methods or to the reference standard used to assess error.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Pfitzner et al reported similar findings, with tibial component alignment of 1.0°, with a 3% outlier (±3°from neutral) rate, and femoral component alignment of 1.0°, with a 3% outlier (±3°from [32,42]. Some of the variability in results may relate to particular surgical methods or to the reference standard used to assess error.…”
Section: Discussionmentioning
confidence: 78%
“…Nam et al also reported excellent results with KA2, noting 0.04°variation from the tibial mechanical axis with no outliers (beyond ±3°from neutral), and −0.1°variation from femoral mechanical axis with 1.3% outliers (beyond ±3°from neutral) [30]. Prior literature pertaining to VISIONAIRE TKAs is conflicting, with some studies reporting good results [9,10,34] and others reporting unsatisfactory results [21,32,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also have been involved in several trials of patientspecific instrumentation (PSI) on both UKA and TKA in the last several years [1,5,6], highlighting the frequency of outliers, the proportion of PSI procedures that needed to be aborted or modified during surgery, as well as the additional costs incurred by the new technology both directly and in terms of the surgeon's time. We initially hypothesized [4] that PSI could be a useful tool for UKA, particularly to improve the tibial cut.…”
mentioning
confidence: 99%